1997
DOI: 10.1016/s0896-6273(00)80417-1
|View full text |Cite
|
Sign up to set email alerts
|

Two period Homologs: Circadian Expression and Photic Regulation in the Suprachiasmatic Nuclei

Abstract: We have characterized a mammalian homolog of the Drosophila period gene and designated it Per2. The PER2 protein shows >40% amino acid identity to the protein of another mammalian per homolog (designated Per1) that was recently cloned and characterized. Both PER1 and PER2 proteins share several regions of homology with the Drosophila PER protein, including the protein dimerization PAS domain. Phylogenetic analysis supports the existence of a family of mammalian per genes. In the mouse, Per1 and Per2 RNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
484
5
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(527 citation statements)
references
References 32 publications
35
484
5
3
Order By: Relevance
“…Its expression pattern is similar to that of mPer1 mRNA (Sun et al 1997;Tei et al 1997), except that a smaller transcript was also detected in the liver. The expression of mTim mRNA that occurs in various tissues other than the brain, as with the other clock genes, mPer1, mPer2, mPer3, Clock and Bmal1 (MOP3) (Ikeda & Nomura 1997;King et al 1997;Shearman et al 1997;Sun et al 1997;Tei et al 1997;Takumi et al 1998a,b), suggests that tissue-specific local-oscillators may exist in the peripheral organs.…”
Section: Cloning Of the Mammalian Timeless Cdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression pattern is similar to that of mPer1 mRNA (Sun et al 1997;Tei et al 1997), except that a smaller transcript was also detected in the liver. The expression of mTim mRNA that occurs in various tissues other than the brain, as with the other clock genes, mPer1, mPer2, mPer3, Clock and Bmal1 (MOP3) (Ikeda & Nomura 1997;King et al 1997;Shearman et al 1997;Sun et al 1997;Tei et al 1997;Takumi et al 1998a,b), suggests that tissue-specific local-oscillators may exist in the peripheral organs.…”
Section: Cloning Of the Mammalian Timeless Cdnamentioning
confidence: 99%
“…Recent molecular dissection has revealed that the feedback loop is the basic concept of the circadian oscillator, conserved across the species from Neurospora and Drosophila to mice (Dunlap 1998a,b;Schibler 1998;Young 1998). A mammalian clock gene period consists of a family containing three members (mPer1, mPer2 and mPer3) (Shearman et al 1997;Sun et al 1997;Tei et al 1997;Takumi et al 1998a,b). The transcription of mPer1 is activated by the binding of the CLOCK/BMAL1 hetero-complex, both of which are bHLH-PAS proteins, to the E-boxes in the promoter region of mPer1 (Gekakis et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The hepatic oscillator is centered on a pair of transcriptional activators, BMAL1 (also named Mop3) (Bunger et al, 2000;Hogenesch et al, 1998) and CLOCK (Gekakis et al, 1998;King et al, 1997) and two classes of repressors of the Period (Per) Shearman et al, 1997;Sun et al, 1997;Tei et al, 1997) and Cryptochrome (Cry) gene families (Griffin et al, 1999;Kume et al, 1999;van der Horst et al, 1999;Vitaterna et al, 1999) (Fig. 2).…”
Section: Transcriptional Network Of the Hepatic Circadian Oscillatormentioning
confidence: 99%
“…The first mammalian clock genes were identified in the late 1990s (King et al 1997;Shearman et al 1997;Shigeyoshi et al 1997;Sun et al 1997;Gekakis et al 1998), and they were found to be expressed not only in the SCN but also in many peripheral tissues. These observations did not, however, provide compelling evidence for the presence of clocks in peripheral cell types, because their cyclic expression could have been the result of rhythmic systemic signals controlled by environmental cues and/or by the SCN.…”
Section: Properties Of Peripheral Oscillatorsmentioning
confidence: 99%